Dimorphism of motor skills of 17-19-year-old students from Bydgoszcz - Mirosława Szark-Eckardt; Michalina Kuska; Hanna Żukowska; Małgorzata Pezala; Marek Napierała (Kazimierz Wielki University, 2018)
The purpose of this article was to demonstrate dimorphism in the motor skills of 17-19-year-old students from schools in Bydgoszcz measured using MTSF. The research was conducted among 2,832 students of both sexes (1,686 boys and 1,146 girls) from schools in Bydgoszcz. Dimorphic differences were determined using the Student's t-Test, Mollison's indicators and the T-score. The study results were presented in the graphical and tabular form. The following conclusions were drawn: 1. The older the boys were the better results were achieved in tests including standing long jump, hand-grip dynamometer, pull-ups, 50m sprint, 4 x 10m shuttle run and 1000m sprint, whereas in the case of girls it was hanging on a pull-up bar and 50m sprint. The remaining results were different in terms of the age of respondents. 2. Boys were reported to have better results than girls in all tests and age groups (except for flexibility at the age of 19). Statistical significance at the confidence level of 1% was reported in almost all tests. 3. The largest differences measured by means of Mollison's ratio were observed in the hand-grip test. 4. The results of the students involved in the study expressed in points after calculation according to the T-scale revealed bigger motor skills in girls in all age groups being compared in relation to their peers and only in the group of 19-year-old boys the results proved to be better.